2015
DOI: 10.1002/fut.21736
|View full text |Cite
|
Sign up to set email alerts
|

Spot and Futures Markets Linkages: Does Contango Differ from Backwardation?

Abstract: Recent research has concluded that spot and futures copper returns are more closely correlated during periods of contango than of backwardation. It is argued speculation and investor demand in futures markets should affect spot prices to a much lesser extent during backwardation, due to an infeasible inter‐temporal arbitrage. This article expands this line of research by analyzing daily spot and 3‐, 15‐, and 27‐month futures contract prices for industrial metals traded on the London Metal Exchange over a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Gulley and Tilton (2014) find strong correlation coefficients between changes in copper spot and futures prices during 1994−2011 when the market stays in strong contango to support their framework empirically. This finding contrasts with that of Fernandez (2016a) which indicates that spot and futures markets for aluminum, copper, lead, nickel, tin, and zinc are weakly correlated during the contango period. Fernandez (2016b) further takes the sign of the interest‐adjusted basis or spread (storage cost minus convenience yield) to examine correlations between spot and futures prices for these selected metals.…”
Section: The Evolution Of Informational Efficiency From 1934 To 2020:...contrasting
confidence: 92%
See 1 more Smart Citation
“…Gulley and Tilton (2014) find strong correlation coefficients between changes in copper spot and futures prices during 1994−2011 when the market stays in strong contango to support their framework empirically. This finding contrasts with that of Fernandez (2016a) which indicates that spot and futures markets for aluminum, copper, lead, nickel, tin, and zinc are weakly correlated during the contango period. Fernandez (2016b) further takes the sign of the interest‐adjusted basis or spread (storage cost minus convenience yield) to examine correlations between spot and futures prices for these selected metals.…”
Section: The Evolution Of Informational Efficiency From 1934 To 2020:...contrasting
confidence: 92%
“…In this regard, researchers have presented their studies on the causal relation, co‐integration, contango, backwardation, and price discovery in spot–futures relations. (Alquist et al., 2013; Arfaoui, 2018; Fernandez, 2016a, 2016b; Go & Lau, 2017a, 2017b; Gulley & Tilton, 2014; Mahalik et al., 2014; McKenzie & Holt, 2002; Silvapulle & Moosa, 1999; Tilton et al., 2011; Westerlund & Narayan, 2013; Wu & McCallum, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Tilton et al [29] propose a theoretical framework in which an increase in futures prices should influence spot prices in strong contango, but not in backwardation. This claim is empirically supported by Gulley and Tilton [10] for copper prices and Fernandez [11] for a broader group of commodities. In the same vein, Almansour [12] demonstrate that for energy commodities, the dynamics of the basis is well described by a regime-dependent process, which allows contango and backwardation regimes to be identified.…”
Section: Futures Prices As a Benchmark For Nominal Pricesmentioning
confidence: 72%
“…There are also studies showing that the joint dynamics of spot and futures is regime dependent. For example, Huang et al [9], Gulley and Tilton [10] and Fernandez [11] demonstrated that spot and futures prices are more correlated in contango than in backwardation. In turn, Almansour [12] demonstrated that the dynamics of the basis for energy commodities is well described by a regime switching process, which allows to identify contango and backwardation regimes.…”
Section: Futures Prices As a Benchmark For Nominal Pricesmentioning
confidence: 99%
“…However, their findings are less supportive of such a hypothesis. For instance, Fernandez (2015) extends the scope of the study by including traded aluminium, copper, lead, nickel, tin and zinc in the London Metal Exchange during the sample period of 1992-2014. After controlling conditional heteroscedasticity in returns, detecting unconditional mean-return breakpoints, and detecting and removing outlying observations, the author finds that the existence of a weak linkage between spot and futures markets during the contango period.…”
Section: Literature Reviewmentioning
confidence: 99%